2013
DOI: 10.1159/000342400
|View full text |Cite
|
Sign up to set email alerts
|

Life and Dinner under the Shared Umbrella: Patterns in Felid and Primate Communities

Abstract: Sympatry between primates and felids is potentially relevant to both their behavioural ecology and their conservation. This paper briefly introduces felids and primates, for the purposes of assessing their interrelationships and the patterns in their spatial congruence using IUCN spatial data. First, we review evidence and opportunity for predator-prey interactions between the felids and primates. Second, we analyse the overlap between species of the two taxa to reveal the potential of particular felid species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Clouded leopards exhibited the closest spatial and temporal associations with muntjac. A study in Borneo on the interactions between felids and primates reported a clouded leopard killing a pig-tailed macaque [ 40 ]. Physiologically, clouded leopards have the longest canines, of any felid species relative to their body size and are likely to have evolved to be able to kill larger-bodied prey such as young muntjac, adult mouse deer and great argus pheasant.…”
Section: Discussionmentioning
confidence: 99%
“…Clouded leopards exhibited the closest spatial and temporal associations with muntjac. A study in Borneo on the interactions between felids and primates reported a clouded leopard killing a pig-tailed macaque [ 40 ]. Physiologically, clouded leopards have the longest canines, of any felid species relative to their body size and are likely to have evolved to be able to kill larger-bodied prey such as young muntjac, adult mouse deer and great argus pheasant.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative data regarding the diet preferences of Sunda clouded leopards are lacking but incidental reports and observations from Borneo (e.g. Rabinowitz et al, 1987; Yeager, 1991; Matsuda et al, 2008; Burnham et al, 2012) suggest that they exploit a diverse array of mammals, and studies of temporal activity overlaps and patterns of co-occurrence with potential prey (Ross et al, 2013) indicate that ungulates may be a key resource. Thus, the response of Sunda clouded leopards to anthropogenic disturbance may be mediated largely by the responses of their prey to such habitat modification.…”
Section: Introductionmentioning
confidence: 99%
“…Densities were estimated using spatially explicit capturerecapture (SCR) models under the Bayesian framework (Royle et al 2014;Meredith 2020a). The R packages secr (Efford 2020), rgdal (Bivand et al 2016), raster (Bivand et al 2016), and makeJAGSmask (Meredith 2020b) were used for importing and formatting capture histories and creating the state space. We ran two models: (1) a spatial model with elevation as a covariate assuming that their densities would vary across the elevational gradient, and (2) capture probability (p) and scale parameter (σ) as a function of sex (Sollmann et al 2011;Webb et al 2020).…”
Section: Density Estimationmentioning
confidence: 99%